The Practice of Breast Self-Examination (SADARI) in Adolescent Based on Knowledge: Praktik Pemeriksaan Payudara Sendiri (SADARI) pada Remaja Putri Berdasarkan Pengetahuan - Dwitania, Erina Febi; Azizah, Nurul; Rosyidah, Rafhani (Universitas Muhammadiyah Sidoarjo, 2021)
The highest incidence rate of women is breast cancer which is 42.1 per 100,000 people with an average death of 17 per 100,000 people. the prevalence of tumors/cancer in Indonesia showed an increase from 1.4 per 1000 people in 2013 to 1.79 per 1000 people in 2018. Breast cancer attacks woman over the age of 50,and has now begun attacking women at a younger age. The design of this research is descriptive with the survey method with the Cross Sectional approach. The entire population of this study was sampled as many as 35 students, research subjects with the criteria of teenage girls in the Health Information Program, Faculty of Health Sciences, Muhammadiyah Sidoarjo University. Data collection using primary data through questionnaires. The questionnaire detailed early detection knowledge of breast cancer and SADARI techniques. Dissemination of questionnaires through google form software and shared online with respondents. From the results of the study, it can be found that out of 35 respondents who practice sadari enough and knowledgeable as many as 14 respondents (73.7%). In this study also the effect of the knowledge that the majority of respondents have is sufficient. Quite a lot of information is also related in doing sadari practice sufficiently. The conclusion of this study is that adolescent knowledge of early detection of breast cancer based on SADARI practices is largely sufficient.